An ethnography of creative practice in forensic mental health - Joyes, Emma (2019)
This original research was funded institutionally as part of a larger AHRC/RCUK Connected Communities programme grant (AH/K003364/1), ‘Creative Practice as Mutual Recovery’ (CPMR) which critically investigated how creative practices may afford an opportunity for mutual recovery. The CPMR programme aimed to extend the notion of mental health recovery beyond individual patients to include other participating members, for example, informal carers, healthcare practitioners, volunteers. The notion that creative practices could foster and connect communities to enhance mental health and wellbeing was a central theme to the programme of research. This thesis focuses uniquely on the potential for creative practice to promote mutuality within a forensic mental health setting. The thesis adopts an ethnographic research design congruent with the exploratory nature of the aims of this project. The research design is purposely iterative, exploring the concepts such as creative practice, wellbeing, and the emergent concept of ‘mutual recovery’ within an interpretivist tradition. The thesis investigates creative practice across three units within one inpatient forensic mental health hospital in the UK. The methods include overt participant observation and semi-structured interviews. The thesis presents an innovative microsociological model for understanding mutuality through creative practices within forensic mental health. This new theoretical model draws on Interaction Ritual Theory to explore the creative practice rituals observed during the fieldwork and to consider their contribution to wellbeing, social connectedness, and mutuality. The observations and interviews established three key contextual features of life which were found to influence creative practices, wellbeing, social connectedness, and mutuality in the forensic setting: a) surveillance, security and risk; b) the emotive environment; and c) boundaried relationships. The study found that mutuality is constrained within the forensic mental health inpatient context. However, it also identified that when hierarchies are less prominent or foregrounded, engagement in creative practices can contribute to the wellbeing of residents and staff and promote social connectedness. This thesis argues that the forensic mental health environment can present challenges to creative practice and notions of mutuality due to a culture of risk, boundaried practices, and highly emotive interactions that occur there. Other societal influences, such as sexism and racism, also present challenges to creative practices and notions of mutuality within the therapeutic setting.